2022
DOI: 10.1002/anie.202204262
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Metalating Efficiency of the Sodium Amide NaTMP in Arene Borylation Applications

Abstract: Though LiTMP (TMP=2,2′,6,6′‐tetramethylpiperidide) is a commonly used amide, surprisingly the heavier NaTMP has hardly been utilised. Here, by mixing NaTMP with tridentate donor PMDETA (N,N,N′,N′′,N′′‐pentamethyldiethylenetriamine), we provide structural, and mechanistic insights into the sodiation of non‐activated arenes (e.g. anisole and benzene). While these reactions are low yielding, adding B(OiPr)3 has a profound effect, not only by intercepting the CAr‐Na bond, but also by driving the metalation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…However, sodium bases, such as NaTMP, hold a great potential for accessing new synthetic landscape. Recently, our laboratory has reported the combination of this base with the tridentate donor PMDETA ( N , N , N ′, N ′′, N ′′‐pentamethyldiethylenetriamine) and B(O i Pr) 3 for the selective deprotonative borylation of inactivated arenes, [31] which could be cross‐coupled to give a new versatile route to the synthesis of biaryl motifs. Here, we illustrate this approach with 1‐methoxynaphthalene, which can be easily borylated and directly coupled with an aryl bromide to obtain the corresponding biaryl product in a 60 % isolated yield ( Scheme 3 ,a ).…”
Section: Discussionmentioning
confidence: 99%
“…However, sodium bases, such as NaTMP, hold a great potential for accessing new synthetic landscape. Recently, our laboratory has reported the combination of this base with the tridentate donor PMDETA ( N , N , N ′, N ′′, N ′′‐pentamethyldiethylenetriamine) and B(O i Pr) 3 for the selective deprotonative borylation of inactivated arenes, [31] which could be cross‐coupled to give a new versatile route to the synthesis of biaryl motifs. Here, we illustrate this approach with 1‐methoxynaphthalene, which can be easily borylated and directly coupled with an aryl bromide to obtain the corresponding biaryl product in a 60 % isolated yield ( Scheme 3 ,a ).…”
Section: Discussionmentioning
confidence: 99%
“…Deuterated benzene was chosen for this purpose, as it is the cheapest commercially available deuterated arene molecule. It has been used previously as a deuterium source in transition-metal-catalyzed and acid-catalyzed HIE, ,, and it can undergo borylation by the previously mentioned NaTMP/B­(O i Pr) 3 combination . To test our hypothesis, we added a catalytic amount of NaTMP (10 mol %) and the donor molecule PMDETA ( N , N , N ′, N ″, N ″-pentamethyldiethylenetriamine) (10 mol %) to a solution of anisole ( 1a ) in C 6 D 6 .…”
mentioning
confidence: 96%
“…Previous studies have shown that addition of TMEDA in hexane induces the deaggregation of NaTMP from a nonsolvated trimer to a dimer (Figure ), while addition of anisole to a mixture of NaTMP and TMEDA or PMDETA allows the isolation of mixed aggregates [(L) 2 Na 2 (TMP)­(C 6 H 4 –OMe)] (L = TMEDA, 3a ; L = PMDETA, 3b ) . These sodium mixed aggregates showed an incomplete metalation of anisole (36% after iodolysis), which was attributed to the equilibrium between the starting materials (L)­NaTMP and anisole with product 3 and TMP­(H) ( vide infra ).…”
mentioning
confidence: 98%
See 2 more Smart Citations